DOUBLE CONFORMITY IN COLOMBIA. THE IMPORTANCE OF REGULATORY REFORM - Centeno Cardona, Elkin (2025)
This study offers a critical legal analysis of the concept of double conformity in Colombia, taking as its starting point the case of former Minister Arias Leiva and the public and institutional debate it sparked.